Unusual foreign bodies causes obstruction of the esophagus in dogs - Elhmri, Khaled M.A. Hussin; Hegazi, Ashraf abdel-hamed (Al-Mukhtar Journal of Sciences, 2008)
Five dogs of ages from 3 month to one year with esophageal obstruction had been treated two cases by surgical correction .The foreign body diagnosed through the history from the owners about foreign bodies in the esophagus, clinical symptoms, X-Ray on the first case and by clinical examination. Treated the first dog by esophagotomy to remove metal wire about 20 cm in length and 2.5 mm in thickness which removed after cutting it into two parts the upper part removed from the oral cavity and the lower part removed from the esophageal incision but the 2nd. dog removed foreign body(bone in the form of T shape) about 4cm in length and 1.5 cm in thickness. The other 3 cases removed the foreign bodies by pushing it toward the mouth cavity by hand & removed by forceps (the foreign bodies near the esophageal in trance).